Pengaruh Gaya Kepemimpinan dan Komunikasi terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening di PT. Cipta Selera Semesta Banten - Kodir; Noor, Muhammad Irawan (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2026)
This study aims to determine the leadership style and communication on employee performance with job satisfaction as an intervening variable at PT. Cipta Selera Semesta Banten. The study was conducted at PT. Cipta Selera Semesta with a sample of employees of PT. Cipta Selera Semesta Banten. The sampling technique used in this study used a saturated sampling technique. The data analysis method used path analysis. The results of the study indicate that: 1) There is a positive and significant influence of leadership style on employee performance at PT. Cipta Selera Semesta; 2) There is a positive and significant influence of communication on employee performance at PT. Cipta Selera Semesta; 3) There is a positive and significant influence of job satisfaction on employee performance at PT. Cipta Selera Semesta; 4) There is a positive and significant influence of leadership style on job satisfaction at PT. Cipta Selera Semesta; 5) There is a positive and significant influence of communication on job satisfaction at PT. Cipta Selera Semesta; 6) Job satisfaction is unable to mediate the influence of leadership style on employee performance; and 7) Job satisfaction is unable to mediate the influence of communication on employee performance.